2017
DOI: 10.1210/jc.2017-00346
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV as a Prognostic Marker and Therapeutic Target in Papillary Thyroid Carcinoma

Abstract: Increased DPP4 expression is associated with cellular invasion and more aggressive disease in papillary thyroid cancer. Targeting DPP4 may be a therapeutic strategy for DPP4-expressing thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…This is in keeping with the experimental evidence that TGFBR2 overexpression may reduce tumorigenicity and metastatic potential of thyroid follicular cells . Targeting transforming growth factor‐β signaling has emerged as a topic of great interest in the management of thyroid cancer …”
Section: Discussionsupporting
confidence: 80%
“…This is in keeping with the experimental evidence that TGFBR2 overexpression may reduce tumorigenicity and metastatic potential of thyroid follicular cells . Targeting transforming growth factor‐β signaling has emerged as a topic of great interest in the management of thyroid cancer …”
Section: Discussionsupporting
confidence: 80%
“…In addition to MYC‐dependent and independent cell proliferation, transforming growth factor‐β may modulate telomerase activity of thyroid cancer cells . The transforming growth factor‐β signaling pathway is known to play an important role in cellular migration/invasion of PTC . Overall, aberrant growth due to senescence resistance as well as enhanced metastatic capacity may collaboratively confer an unfavorable prognosis in patients with TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the combination of metformin with sitagliptin showed a greater reduction in the number of metastatic lung nodules than treatment with metformin or sitagliptin alone . In the mouse xenograft model with papillary thyroid cancer, sitagliptin use was associated with reduced tumor growth, with the transforming growth factor‐β signaling pathway being potentially involved . In contradiction to these findings, Wang et al demonstrated in an in‐vivo study that use of DPP4 inhibitors increased the risk of metastasis in colon, hepatic, lung, ovary, and melanoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in tumor biology by acting as a tumor suppressor or activator depending upon the level of expression and its interaction with the microenvironment and selected chemokines . In animal models, DPP4/CD26 expression has been shown to be of prognostic value and is a potential therapeutic target in various malignancies . Of note is that the first phase I clinical trial involving CD26‐expressing cancers with an anti‐CD26 monoclonal antibody was recently completed and reported prolonged disease stabilization in patients with mesothelioma with good drug tolerance …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation